2017
DOI: 10.1038/s41598-017-03423-3
|View full text |Cite
|
Sign up to set email alerts
|

Transient cell assembly networks encode stable spatial memories

Abstract: One of the mysteries of memory is that it can last despite changes in the underlying synaptic architecture. How can we, for example, maintain an internal spatial map of an environment over months or years when the underlying network is full of transient connections? In the following, we propose a computational model for describing the emergence of the hippocampal cognitive map in a network of transient place cell assemblies and demonstrate, using methods of algebraic topology, how such a network can maintain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…Second, line or ring formations would often break apart and re-form new configurations that typically involved other agents or formations that were able to phase-synchronize with elements of the subgroup. These alternating disintegrative and aggregative dynamics may be consistent with analyses of persistent homologies in place-cell networks with transient connectivity (Babichev and Dabaghian, 2017).…”
Section: Emergent Swarming Behaviorssupporting
confidence: 81%
“…Second, line or ring formations would often break apart and re-form new configurations that typically involved other agents or formations that were able to phase-synchronize with elements of the subgroup. These alternating disintegrative and aggregative dynamics may be consistent with analyses of persistent homologies in place-cell networks with transient connectivity (Babichev and Dabaghian, 2017).…”
Section: Emergent Swarming Behaviorssupporting
confidence: 81%
“…In the current model, enabled by a much more powerful Zigzag persistent homology theory [ 34 36 ], we employ an alternative approach, in which the links of the coactivity graph appear instantly following pairwise place cell coactivity events. Thus, in contrast with the model discussed in [ 58 ], the current model involves no selection of the “winning” coactivity links, which one might hold responsible for stabilizing the shapes of the flickering coactivity complexes. Nevertheless, this model demonstrates the same effect: the large-scale topological shapes of resulting coactivity complexes stabilize, given that the connections decay sufficiently slowly and have sufficiently broadly distributed lifetimes.…”
Section: Discussionmentioning
confidence: 88%
“…Previously, we investigated this effect using an alternative model of transient cell assemblies, in which the connections were constructed by identifying the pool of cells that spike within a certain “coactivity window,” , and building the coactivity graph from the most frequently cofiring pairs of neurons [ 58 ]. The accumulation of topological information within each -period, was then described using persistent homology theory techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The algebraic-topological properties of the coactivity complexes were studied in Dabaghian et al ( 2012 ), Babichev et al ( 2016b ), and Babichev and Dabaghian ( 2017a , b ). There it was demonstrated that if place cell populations operate within biological parameters, then the number of topological loops in different dimensions of the coactivity complex—the Betti numbers (Munkres, 2000 )—match the Betti numbers of the environment .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the learning times and other global characteristics of produced via algebraic topology techniques are insensitive to many details of the place cell spiking activity (Dabaghian et al, 2012 ; Babichev et al, 2016b ; Babichev and Dabaghian, 2017a , b ). For example, the learning time T min depends mostly on the mean place field sizes and the mean peak firing rates, but it does not depend strongly on the spatial layout of the place fields or on the limited spiking variations.…”
Section: Resultsmentioning
confidence: 99%